2018
DOI: 10.3389/fmicb.2018.02582
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Responses of Potato (Solanum tuberosum L.) Plants to Heat Stress and Infection With Potato Virus Y

Abstract: Potato (Solanum tuberosum) plants are exposed to diverse environmental stresses, which may modulate plant–pathogen interactions, and potentially cause further decreases in crop productivity. To provide new insights into interactive molecular responses to heat stress combined with virus infection in potato, we analyzed expression of genes encoding pathogenesis-related (PR) proteins [markers of salicylic acid (SA)-mediated plant defense] and heat shock proteins (HSPs), in two potato cultivars that differ in tole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 70 publications
3
66
1
Order By: Relevance
“…A recent study on Potato Virus Y (PVY) in potato thermo-tolerant and sensitive genotypes under heat stress, HSPs was induced in both genotypes. Regarding thermo-tolerant genotypes, the expression of PR genes was also high, resulting in less viral infection [117]. Resistance against viral infection in Cytosinpeptidemycin application for the control of Rice Black Streaked Dwarf Virus (RBSDV), along with other defense-related genes, antioxidant enzymes and HSP also were up-regulated to control the virus infection [115].…”
Section: Role Of Hsps In Plant Defensementioning
confidence: 99%
“…A recent study on Potato Virus Y (PVY) in potato thermo-tolerant and sensitive genotypes under heat stress, HSPs was induced in both genotypes. Regarding thermo-tolerant genotypes, the expression of PR genes was also high, resulting in less viral infection [117]. Resistance against viral infection in Cytosinpeptidemycin application for the control of Rice Black Streaked Dwarf Virus (RBSDV), along with other defense-related genes, antioxidant enzymes and HSP also were up-regulated to control the virus infection [115].…”
Section: Role Of Hsps In Plant Defensementioning
confidence: 99%
“…There is a high degree of cross-kingdom functional conservation of subnuclear bodies. Both the nucleolus and CBs have been implicated in responses to a wide range of biotic and abiotic stresses (Boulon et al, 2010;Bassett, 2012;Love et al, 2017;Makarova et al, 2018). It will be of substantial interest to discover the extent to which coilin operates as a mediator for sensing and triggering of defence against these stresses in plants and other eukaryotic systems.…”
Section: Researchmentioning
confidence: 99%
“…With regard to PVY, we have recently shown that susceptibility of potato cv. Chicago plants to systemic PVY infection (virus accumulation and symptom production in systemically infected leaves) is significantly enhanced by elevated temperature compared with normal conditions (Makarova et al, 2018). Interestingly, such an enhanced susceptibility was correlated with reduced expression of genes encoding pathogenesis-related (PR) proteins, which are hallmarks of salicylic acid (SA)-mediated plant defence responses.…”
Section: Introductionmentioning
confidence: 99%